Endometrial response to IVF hormonal manipulation: Comparative analysis of menopausal, down regulated and natural cycles - Gayer Nalini; Hosie Margot J; Terry Vera; Adams Susan M; Murphy Christopher R (BMC, 2004)
Abstract Background Uterine luminal epithelial cell response to different hormonal strategies was examined to determine commonality when an endometrium attains a receptive, stimulated, morphological profile that may lead to successful implantation. Methods Endometrial biopsies from 3 cohorts of patients were compared. The tissue samples taken from these patients were categorized into 8 different groups according to their baseline and the hormone regime used. Results Pre-treatment natural cycle tissue was variable in appearance. Downregulation with a GnRH analogue tissue appeared menopausal in character. HRT after downregulation resulted in tissue uniformity. HRT in menopause resulted in a 'lush' epithelial surface. HST in the natural cycle improved the morphology with significant difference in secretion between the two regimes examined. Conclusions Down regulation plus HRT standardized surface appearance but tissue response is significantly different from the natural cycle, natural cycle plus HRT or menopause plus HRT. HRT in menopause reinstates tissue to a state similar to a natural cycle but significantly different from a natural cycle plus HST. HST with a natural cycle is similar to tissue from the natural cycle but significant differences reflect the influence of the particular hormones present (at any point) within the cycle.